Accountability and Transparency Practices in Village Fund Governance - Lailatul Widiya Astutik; Hadiah Fitriyah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Village fund governance remains a central issue in achieving accountable local administration and sustainable community development. Specific Background: In Indonesia, the Alokasi Dana Desa (ADD) is designed to support village development and community empowerment, yet its management often faces administrative and participatory challenges. Knowledge Gap: Empirical evidence describing how accountability and transparency are practiced at the village level and how these practices relate to development outcomes is still limited. Aims: This study examines the implementation of accountability and transparency in managing ADD in Grinting Village, Sidoarjo Regency. Results: Using a descriptive qualitative approach through observations, interviews, and document analysis, the findings show that open reporting mechanisms, community involvement, and adherence to regulatory standards contribute to orderly financial administration and increased public trust. However, limitations remain in the capacity of village officials and the consistency of periodic reporting. Novelty: This study provides a detailed process-based account of ADD governance aligned with national regulations at the village level. Implications: The findings suggest that strengthening administrative capacity and public literacy is essential for sustaining accountable village governance and supporting equitable community development.